Clinical-epidemiological profile of children and adolescents hospitalized in the pediatric surgery nurse in a reference hospital in Rio de Janeiro (Research, Society and Development, 2022)
Scientific-technological advances in health resulted in an increase in child survival, due to the implementation of health promotion and protection policies. However, a new pediatric clientele has emerged, presenting complex health care demands. To describe the profile of children and adolescents hospitalized in the pediatric surgery ward at a reference hospital in Rio de Janeiro, Brazil. Retrospective study, carried out in the pediatric surgery ward of a national reference institution in pediatrics, from July 2015 to July 2016, after approval by the institution's CEP n° 1584986/2016. Among the 204 children and adolescents, (63.7%) were male, black (54.4%), in the infant (41.6%) and preschool age group (35.8%), lived outside the city where the hospital was located (54.8%), and (55.4%) were monitored by the hospital. The most prevalent diagnoses were congenital malformations (79.2%), the most prominent surgical procedures were the creation of ostomies, the correction of hypospadias and the reconstruction of the intestinal transit. The length of hospital stay ranged from 1 to 4 days (34.3%) and from 8 to 14 days (28.9%). It was found that the clientele is characterized by children and adolescents with special health needs and chronically ill, and that knowing the profile shows essential information in order to contribute to the planning and organization of the care provided in the pediatric surgery ward.